A Patient with Erdheim-Chester Disease Limited to Central Nervous System - Rajesh K. Gupta; Anam Haque; Thejasvi A. Reddy; Carlos A. Pérez (MDPI AG, 2022)
Erdheim-Chester disease (ECD) is a rare, sporadic, non-Langerhans cell histiocytosis, a multisystem disorder, which has higher mortality when presented with CNS involvement. We report a 46-year-old woman who has ECD with exclusive CNS involvement. She presented with intracranial hemorrhage and had a poor response to corticosteroid and interferon. She required multiple debulking procedures and eventually responded well to cobimetinib. She has not had any other organ involvement thus far. This report highlights that CNS involvement may be the only manifestation of ECD and sometimes may require a repeat biopsy with IHC testing for excellent treatment outcomes.